BLOCKCHAIN AS A PARADIGM SHIFTER: A LITERATURE REVIEW OF POTENTIAL AND IMPLEMENTATION BARRIERS - Loso Judijanto; Al-Amin (CV. Adiba Aisha Amira, 2024)
This research aims to investigate the potential and barriers of blockchain technology implementation through a comprehensive literature review. Blockchain is recognised as one of the most transformative technological innovations in recent decades, with the ability to improve transparency, data security, and operational efficiency across a wide range of industry sectors, including finance, supply chain, and healthcare. However, the adoption of this technology is still faced with a number of significant challenges. Key barriers include scalability issues, regulatory uncertainty, and concerns related to security and privacy. The study highlights the importance of developing more advanced and scalable technologies, establishing clear and flexible regulations, and intensifying educational efforts to increase blockchain literacy and adoption. In conclusion, despite the challenges, cooperation between various stakeholders can optimise blockchain's potential as a paradigm-shifter in various industry sectors.